2020
DOI: 10.34172/ehem.2020.33
|View full text |Cite
|
Sign up to set email alerts
|

A new approach for designing a hypolimnetic oxygenation system to improve the water quality in tropical reservoirs

Abstract: Background: One of the most important problems of dams is thermal layering which directly affects the water quality. This study was performed to propose a solution to increase the water quality of the Esteghlal Dam reservoir in Minab, Hormozgan. Methods: The water quality of Esteghlal Dam was evaluated from 2016 to 2018. During this period, 18 samples were collected from three different points of the dam. The parameters of water temperature, electrical conductivity, total dissolved solids, total suspended soli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…However, natural activities threaten the water quality, therefore, constant and proper monitoring of the reservoir is necessary. According to the study of Moridi et al, water in reservoir can be affected by point and non-point sources of contamination (9). In addition, the physical, chemical and biological conditions of stored water may be worsened by storage in reservoir (9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, natural activities threaten the water quality, therefore, constant and proper monitoring of the reservoir is necessary. According to the study of Moridi et al, water in reservoir can be affected by point and non-point sources of contamination (9). In addition, the physical, chemical and biological conditions of stored water may be worsened by storage in reservoir (9).…”
Section: Introductionmentioning
confidence: 99%
“…According to the study of Moridi et al, water in reservoir can be affected by point and non-point sources of contamination (9). In addition, the physical, chemical and biological conditions of stored water may be worsened by storage in reservoir (9). UNEP reported that monitoring of freshwaters is the first action to be taken to prevent the increase of pollution, and also, to restore polluted water bodies (10).…”
Section: Introductionmentioning
confidence: 99%